A Study on the Motivational Mechanism of Creative Situations - Jian, Z.; Qian, Y.; Fei, Z. (Journal of Comparative International Management, 2006)
Using the organismic dialectical metatheory and the empirical research approach, this study systemically explores the relationship between creative situations and creative behavior. The study finds that the opinion proposed by organismic dialectical metatheory, that needs and motivation mediate the situation and the behavior, is true. Also, support from leaders and the richness of resources are primary components of creative situations. Furthermore, the satisfaction of self-determination and competence is at the core of creative activity; enjoyment is the direct cause for creative behavior, and pursuit of challenges is the most important indirect cause.